Identification of the self-purification stretches of the Pinios River, Central Greece - CHATZINIKOLAOU, Y.; LAZARIDOU, M. (Mediterranean Marine Science, 2007)
The Pinios River basin in Thessaly, Greece, is intensively farmed and heavily polluted with poorly treated domestic and industrial waste. The river was divided into 35 homogenous stretches. We investigated the self-purification capacity along the different stretches of the Pinios based on the responses of the benthic macroinvertebrate community to municipal, industrial and agricultural pollution in the basin. Water quality was assessed by the performance of six diversity and biotic indices and scores for assessing water quality. Self-purification found by the downstream amelioration of water quality was evident at five stretches. These stretches should be safeguarded and priority should be given to restoration projects along the most water-quality-degraded stretches that lack the capacity for self-purification.